Generalized $$\widetilde{W}$$ W ~ algebras - Yaroslav Drachov (European Physical Journal C: Particles and Fields)
Abstract Recently, a new generalized family of infinite-dimensional $$ \widetilde{W} $$ W ~ algebras, each associated with a particular element of a commutative subalgebra of the $$ W_{1+∞ } $$ W 1 + ∞ algebra, was described. This paper provides a comprehensive account of the aforementioned association, accompanied by the requisite proofs and illustrative examples. This approach allows a derivation of Ward identities for selected WLZZ matrix models and the expansion of corresponding $$ W $$ W -operators in terms of an infinite set of variables $$ p_k $$ p k .